Commanding the Red Army's Sherman tanks : the World War II memoirs of Hero of the Soviet Union, Dmitriy Loza - Loza, D. F. (Dmitriĭ Fedorovich) (University of Nebraska Press, 1996)
Hero of the Soviet Union Dmitriy Loza has carefully crafted his World War II experiences with U.S.-provided Sherman tanks into a highly readable memoir. Between the fall of 1943 and August 1945, Loza fought in the Ukraine, Romania, Hungary, Czechoslovakia, and Austria. He commanded a tank battalion during much of this period and had three Shermans shot out from under him. Loza's unit participated in such well-known combat actions as the Korsun-Shevchenkovskiy Operation, the Jassy-Kishenev Operation, and the battles for Budapest, Vienna, and Prague. Following the German surrender, Loza's unit was sent to Mongolia, where it participated in the arduous trek across the Gobi Desert to attack the Japanese Kwantung Army in Manchuria. This is the first available detailed examination of the Red Army's exploitation of U.S. war materiel during World War II and one of the first genuine memoirs available from the Russian front. Loza also provides firsthand testimony on tactical command decisions, group objectives and how they were accomplished, and Soviet use of combat equipment and intelligence. Only after the collapse of the USSR and concomitant relaxing of prohibitions against publication of materials related to the Lend-Lease Program there could this account be made available.